Reduction offeacal shedding of parasites in West African dwarf bucks fed yeast and lactobacillus acidophilus (2017)
Ruminants serve as reservoirs of pathogenic microorganisms and their faecal shedding forms the vehicle of entry into human food chain which in turn causes food borne diseases. Usually drugs and live vaccines are the main control measures; however, due to increasing concerns of resistance and residues in meal with prophylactic drug use and the high cost of vaccines, alternative control methods are needed. The aim of this study was to determine if administration of probiotics could influence the shedding of faecal pathogenic bacteria and parasites/helminthes from WAD goats. In a completely randomised design, thirty goats were allotted to six dietary treatments which were formulated using concentrate as: control (Dl); antibiotic (D2); 2.5g bakers yeast (D3); 5. 0g bakers yeast (D4); 2.5g yeast plus Lactobacilli (D5) and 5.0g yeast plus Lactobacilli (D6), where D5 and D6 were fortified with Lactobacillus acidophilus at 1.00x10(12)cfu/g each. Faecal samples (3g) were collected from bucks for faecal egg count reduction test (FECRT, %). Data obtained were subjected to descriptive statistics and ANOVA α(0.05). The results showed that the FECRT (%) for the pathogenic bacteria revealed a significant (p<0.05) reduction in load at two weeks by 99.99 % in D6 while the least was seen in D2 with 98.98 %. The salmonella as at day 14 recorded significant percentage reduction which was high in D5 (90%) and lowest in D6 (19.23 %). The parasitic shedding of coccidia at day 14 showed that the goats on D1 shed 400 egg per gram (epg) while those on D3 recorded 150 epg. The animals on D2, D4, D5 and D6 recorded no trace of coccidia eggs in their faeces while animals on D5 and D6 showed reductions of 5.60 and 50.00 % respectively in Ascaris. Tapeworm was identified only in faecal sample of D1. The result revealed that yeast combined with Lactobacillus acidophilus at 5g/day could serve as a potential alternative to anti-bacteria and anti-helminthes.